Evaluation of Antimicrobial Activity of Some Commonly Used Antibiotics on E. Coli and Klebsiella Species - Bello, L. H.; Joseph, A. A.; Abbati, M. A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Many microorganisms have developed resistance to commonly used antibiotics, constituting a major challenge in management of microbial infections. This study investigates the efficacy of selected antibiotics against two significant bacterial pathogens. Clinical isolates of E. coli and Klebsiella species were obtained from Microbiology department of specialist hospital Gombe and subjected to antibiotic susceptibility testing using the Kirby-Bauer disc diffusion method. The antibiotics tested included Gentamicin, Ofloxacin, Augmentin, Ceftriaxone, Erythromycin, Cloxacillin, Cefuroxime, and Ceftazidime. The results revealed that E. coli exhibited sensitivity to Gentamicin, Ofloxacin, Augmentin, and Ceftriaxone, but resistance to Erythromycin, Cloxacillin, and Ceftazidime. Conversely, Klebsiella species were sensitive to Erythromycin, Cefuroxime, and Ceftazidime, with resistance noted against Gentamicin, Augmentin, and Ceftriaxone. Cefuroxime emerged as the most effective antibiotic against both bacterial species, showing no resistance in either. These findings underscore the critical need for regular antibiotic susceptibility testing to ensure the effective treatment of infections caused by these pathogens, as resistance patterns can significantly impact clinical outcomes.